2020
DOI: 10.5539/jel.v9n5p59
|View full text |Cite
|
Sign up to set email alerts
|

Availability of ISTE Digital Citizenship Standards Among Middle and High School Students and Its Relation to Internet Self-Efficacy

Abstract: The purpose of this study was to gauge the level of availability of ISTE Digital Citizenship standards among middle and high school students in Riyadh, Saudi Arabia. The research employed a quantitative survey approach to measuring the availability of elements of digital citizenship. The survey was administered to a sample of 394 students from several middle and high schools. The survey items were built based on the four domains of digital citizenship by ISTE (Digital identity, Ethical behavior, Intellectual p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…This means that students are keen to pay attention to the digital citizen. This result is supported by Aldosari et al (2020) who showed that students had high levels of Internet self-efficacy and availability of digital citizenship in the first and second domains. Also, Almsiad (2020) in his study claimed that the students believed that they achieved the "digital citizen" standard the most.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…This means that students are keen to pay attention to the digital citizen. This result is supported by Aldosari et al (2020) who showed that students had high levels of Internet self-efficacy and availability of digital citizenship in the first and second domains. Also, Almsiad (2020) in his study claimed that the students believed that they achieved the "digital citizen" standard the most.…”
Section: Discussionmentioning
confidence: 53%
“…There are other studies such as (Nair, 2021;Aldosari et al, 2020;Ayad & Ajrami, 2017) confirm the importance of adopting international technology standards (ISTE, 2016) for students. These standards impact the educational process and the student's technical skills positively.…”
Section: Research Problemmentioning
confidence: 91%
See 2 more Smart Citations
“…This concept of digital citizenship inspired other digital citizenship models, such as by Choi (2018), Common Sense Education (Common Sense Media, 2016), and Singapore cyber wellness secondary school curriculum (MOE Singapore, 2014). As the result, several new elements had been used in digital citizenship definition by several scholars,such as digital identity, online reputation or a digital footprint, and relationships (Martin et al, 2020;Phornprasert et al, 2020;Aldosari et al, 2020).…”
Section: Digital Citizenshipmentioning
confidence: 99%